Lifting and carrying - Safetycare Australia (Australia : Safetycare Australia, 2000)
Material handling occurs in one way or another in every department of every business on every working day - it is not surprising that accidents and injuries resulting from incorrect manual handling techniques comprise the largest group of occupational hazards that result in lost time
Title from title screen
Keywords: Lifting and carrying; Human mechanics; Weight lifting